2019
DOI: 10.1016/j.jesp.2019.103831
|View full text |Cite|
|
Sign up to set email alerts
|

Defending victims of bullying in the classroom: The role of moral responsibility and social costs

Abstract: The current study examined the role of moral responsibility (i.e., moral disengagement) and social costs (i.e., prioritizing popularity and classroom norms) in defending victims of bullying in the classroom. Participants were 1362 students (Age 8-15) from 58 classrooms who completed self-reported measures on moral disengagement and prioritizing popularity and peer-reported measures on bullying and defending. We first examined whether the outcome of the cost-benefit analysis with regard to the social costs of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 68 publications
4
29
2
2
Order By: Relevance
“…Moreover, the current study did not account for classroom-level norms that may influence whether defending is associated with risks for youth. For example, previous research has shown that youth are more likely to defend in classrooms with strong anti-bullying norms (Garandeau et al, 2019;Pouwels et al, 2019). Future research should consider how classroom-level variables, such as bullying norms, relate to the outcomes of defending.…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 99%
“…Moreover, the current study did not account for classroom-level norms that may influence whether defending is associated with risks for youth. For example, previous research has shown that youth are more likely to defend in classrooms with strong anti-bullying norms (Garandeau et al, 2019;Pouwels et al, 2019). Future research should consider how classroom-level variables, such as bullying norms, relate to the outcomes of defending.…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 99%
“…The classroom bullying popularity norm was operationalized as the within-classroom correlation between bullying and perceived popularity. This operationalization was used in at least 11 other studies (e.g., Dijkstra & Gest, 2015;Laninga-Wijnen et al, 2018, 2020Peets et al, 2015;Pouwels et al, 2019). The bullying descriptive norm was operationalized as the classroom average of individual scores in bullying.…”
Section: Classroom-level Variablesmentioning
confidence: 99%
“…Some adolescents use coercive methods to elevate themselves in the social hierarchy (Ojanen & Nostrand, 2014 ), and adolescent bullying is associated with intentional reward motives for aggression (Dumas et al, 2019 ; Runions et al, 2018 ). Adolescents who are motivated to be popular will pay special attention to the potential benefits and cost of bullying behavior (Pouwels et al, 2019 ). If bullying appears to lead to popularity with minimal costs, young people are more likely to involve in bullying (Pan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%